Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Certainly! Let's address each part of your task step-by-step. Make sure to have your graph sheet ready for visual representation and follow along with these detailed instructions.
### Part (a): Completing the Table of Values
Let's work with the equations given:
1. [tex]\( x - 2y = -2 \)[/tex]
2. [tex]\( x - 2y = 2 \)[/tex]
We need to find the [tex]\( y \)[/tex] values corresponding to [tex]\( x \)[/tex] values from [tex]\(-3\)[/tex] to [tex]\(3\)[/tex].
#### For [tex]\( x - 2y = -2 \)[/tex]
Rearranging the equation for [tex]\( y \)[/tex]:
[tex]\[ x - 2y = -2 \][/tex]
[tex]\[ -2y = -2 - x \][/tex]
[tex]\[ y = \frac{x + 2}{2} \][/tex]
Now, let’s determine the [tex]\( y \)[/tex] values for x [tex]\( = -3, -2, -1, 0, 1, 2, 3 \)[/tex]:
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ y = \frac{-3 + 2}{2} = \frac{-1}{2} = -0.5 \][/tex]
- For [tex]\( x = -2 \)[/tex]:
Given: [tex]\( y = 1 \)[/tex] already provided in the table.
- For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = \frac{-1 + 2}{2} = \frac{1}{2} = 0.5 \][/tex]
- For [tex]\( x = 0 \)[/tex]:
Given: [tex]\( y = 1 \)[/tex] already provided in the table.
- For [tex]\( x = 1 \)[/tex]:
[tex]\[ y = \frac{1 + 2}{2} = \frac{3}{2} = 1.5 \][/tex]
- For [tex]\( x = 2 \)[/tex]:
Given: [tex]\( y = 2 \)[/tex] already provided in the table.
- For [tex]\( x = 3 \)[/tex]:
[tex]\[ y = \frac{3 + 2}{2} = \frac{5}{2} = 2.5 \][/tex]
So, the completed table for [tex]\( x - 2y = -2 \)[/tex]:
\begin{tabular}{|c|c|c|c|c|c|c|c|}
\hline
[tex]$x$[/tex] & -3 & -2 & -1 & 0 & 1 & 2 & 3 \\
\hline
[tex]$x - 2y = -2$[/tex] & -0.5 & 1 & 0.5 & 1 & 1.5 & 2 & 2.5 \\
\hline
\end{tabular}
#### For [tex]\( x - 2y = 2 \)[/tex]
Rearranging the equation for [tex]\( y \)[/tex]:
[tex]\[ x - 2y = 2 \][/tex]
[tex]\[ -2y = 2 - x \][/tex]
[tex]\[ y = \frac{x - 2}{2} \][/tex]
Now, let’s determine the [tex]\( y \)[/tex] values for [tex]\(x\)[/tex] from [tex]\(-3\)[/tex] to [tex]\(3\)[/tex]:
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ y = \frac{-3 - 2}{2} = \frac{-5}{2} = -2.5 \][/tex]
- For [tex]\( x = -2 \)[/tex]:
Given: [tex]\( y = -2 \)[/tex] already provided in the table.
- For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = \frac{-1 - 2}{2} = \frac{-3}{2} = -1.5 \][/tex]
- For [tex]\( x = 0 \)[/tex]:
Given: [tex]\( y = -1 \)[/tex] already provided in the table.
- For [tex]\( x = 1 \)[/tex]:
[tex]\[ y = \frac{1 - 2}{2} = \frac{-1}{2} = -0.5 \][/tex]
- For [tex]\( x = 2 \)[/tex]:
Given: [tex]\( y = 0 \)[/tex] already provided in the table.
- For [tex]\( x = 3 \)[/tex]:
[tex]\[ y = \frac{3 - 2}{2} = \frac{1}{2} = 0.5 \][/tex]
So, the completed table for [tex]\( x - 2y = 2 \)[/tex]:
\begin{tabular}{|c|c|c|c|c|c|c|c|}
\hline
[tex]$x$[/tex] & -3 & -2 & -1 & 0 & 1 & 2 & 3 \\
\hline
[tex]$x - 2y = -2$[/tex] & -0.5 & 1 & 0.5 & 1 & 1.5 & 2 & 2.5 \\
[tex]$x - 2y = 2$[/tex] & -2.5 & -2 & -1.5 & -1 & -0.5 & 0 & 0.5 \\
\hline
\end{tabular}
### Part (b): Determining the Gradient
To determine the gradient (slope) of the line [tex]\( x - 2y = 2 \)[/tex]:
Rewriting the equation in slope-intercept form [tex]\( y = mx + b \)[/tex] where [tex]\( m \)[/tex] is the slope:
[tex]\[ x - 2y = 2 \][/tex]
[tex]\[ -2y = -x + 2 \][/tex]
[tex]\[ y = \frac{1}{2}x - 1 \][/tex]
Thus, the gradient [tex]\( m \)[/tex] of the line [tex]\( x - 2y = 2 \)[/tex] is:
[tex]\[ m = \frac{1}{2} \][/tex]
### Part (a): Completing the Table of Values
Let's work with the equations given:
1. [tex]\( x - 2y = -2 \)[/tex]
2. [tex]\( x - 2y = 2 \)[/tex]
We need to find the [tex]\( y \)[/tex] values corresponding to [tex]\( x \)[/tex] values from [tex]\(-3\)[/tex] to [tex]\(3\)[/tex].
#### For [tex]\( x - 2y = -2 \)[/tex]
Rearranging the equation for [tex]\( y \)[/tex]:
[tex]\[ x - 2y = -2 \][/tex]
[tex]\[ -2y = -2 - x \][/tex]
[tex]\[ y = \frac{x + 2}{2} \][/tex]
Now, let’s determine the [tex]\( y \)[/tex] values for x [tex]\( = -3, -2, -1, 0, 1, 2, 3 \)[/tex]:
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ y = \frac{-3 + 2}{2} = \frac{-1}{2} = -0.5 \][/tex]
- For [tex]\( x = -2 \)[/tex]:
Given: [tex]\( y = 1 \)[/tex] already provided in the table.
- For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = \frac{-1 + 2}{2} = \frac{1}{2} = 0.5 \][/tex]
- For [tex]\( x = 0 \)[/tex]:
Given: [tex]\( y = 1 \)[/tex] already provided in the table.
- For [tex]\( x = 1 \)[/tex]:
[tex]\[ y = \frac{1 + 2}{2} = \frac{3}{2} = 1.5 \][/tex]
- For [tex]\( x = 2 \)[/tex]:
Given: [tex]\( y = 2 \)[/tex] already provided in the table.
- For [tex]\( x = 3 \)[/tex]:
[tex]\[ y = \frac{3 + 2}{2} = \frac{5}{2} = 2.5 \][/tex]
So, the completed table for [tex]\( x - 2y = -2 \)[/tex]:
\begin{tabular}{|c|c|c|c|c|c|c|c|}
\hline
[tex]$x$[/tex] & -3 & -2 & -1 & 0 & 1 & 2 & 3 \\
\hline
[tex]$x - 2y = -2$[/tex] & -0.5 & 1 & 0.5 & 1 & 1.5 & 2 & 2.5 \\
\hline
\end{tabular}
#### For [tex]\( x - 2y = 2 \)[/tex]
Rearranging the equation for [tex]\( y \)[/tex]:
[tex]\[ x - 2y = 2 \][/tex]
[tex]\[ -2y = 2 - x \][/tex]
[tex]\[ y = \frac{x - 2}{2} \][/tex]
Now, let’s determine the [tex]\( y \)[/tex] values for [tex]\(x\)[/tex] from [tex]\(-3\)[/tex] to [tex]\(3\)[/tex]:
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ y = \frac{-3 - 2}{2} = \frac{-5}{2} = -2.5 \][/tex]
- For [tex]\( x = -2 \)[/tex]:
Given: [tex]\( y = -2 \)[/tex] already provided in the table.
- For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = \frac{-1 - 2}{2} = \frac{-3}{2} = -1.5 \][/tex]
- For [tex]\( x = 0 \)[/tex]:
Given: [tex]\( y = -1 \)[/tex] already provided in the table.
- For [tex]\( x = 1 \)[/tex]:
[tex]\[ y = \frac{1 - 2}{2} = \frac{-1}{2} = -0.5 \][/tex]
- For [tex]\( x = 2 \)[/tex]:
Given: [tex]\( y = 0 \)[/tex] already provided in the table.
- For [tex]\( x = 3 \)[/tex]:
[tex]\[ y = \frac{3 - 2}{2} = \frac{1}{2} = 0.5 \][/tex]
So, the completed table for [tex]\( x - 2y = 2 \)[/tex]:
\begin{tabular}{|c|c|c|c|c|c|c|c|}
\hline
[tex]$x$[/tex] & -3 & -2 & -1 & 0 & 1 & 2 & 3 \\
\hline
[tex]$x - 2y = -2$[/tex] & -0.5 & 1 & 0.5 & 1 & 1.5 & 2 & 2.5 \\
[tex]$x - 2y = 2$[/tex] & -2.5 & -2 & -1.5 & -1 & -0.5 & 0 & 0.5 \\
\hline
\end{tabular}
### Part (b): Determining the Gradient
To determine the gradient (slope) of the line [tex]\( x - 2y = 2 \)[/tex]:
Rewriting the equation in slope-intercept form [tex]\( y = mx + b \)[/tex] where [tex]\( m \)[/tex] is the slope:
[tex]\[ x - 2y = 2 \][/tex]
[tex]\[ -2y = -x + 2 \][/tex]
[tex]\[ y = \frac{1}{2}x - 1 \][/tex]
Thus, the gradient [tex]\( m \)[/tex] of the line [tex]\( x - 2y = 2 \)[/tex] is:
[tex]\[ m = \frac{1}{2} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.